RETRACTED: Assessing the Role of Environmental Expenditures and Green Transport in Emissions Released by Transport: An Application of ARDL Approach - Hussain, Zahid; Miao, Cuifen; Zhang, Weitu; Khan, Muhammad Kaleem; Xia, Zhiqing (Frontiers in Environmental Science, 2021)
This study investigates the effects of traffic, transport energy consumption, environmental expenditures and green transport on transport carbon dioxide emissions (TCO2). We employ cross-sectional autoregressive distributed lags for estimation in the short and long runs and examine the panel time-series data from 2000 to 2020 in OECD countries. This method allows heterogeneity in the dependencies and slope parameters across countries. Results demonstrate that road and railway traffic movements increase the amount of TCO2 in the short and long runs. In addition, transport energy consumption is the driving factor in releasing TCO2 in the long run. Moreover, the joint effect of locomotives and transport energy consumption significantly reduces TCO2 in the short run. By contrast, the findings support the argument that environmental expenditures and green transport mitigate TCO2 in the long run. The findings also show an inverted u-shaped relationship between TCO2 and transport energy consumption. With the empirical findings as basis, we suggest that OECD countries should reduce traffic movements and enhance the environmental expenditures so that they may produce green transport vehicles to combat environmental issues.